2010
DOI: 10.1007/s12245-010-0230-8
|View full text |Cite
|
Sign up to set email alerts
|

Acute-on-chronic subdural hematoma

Abstract: A 38-year-old male complains of a right-sided retro-orbitaltemporal headache of 2-day duration. It is described as intermittent and pressure-like, and is preceded by bouts of left arm numbness. He denies diplopia, visual changes, nausea, vomiting, or alterations in his consciousness. No acute trauma is reported, but he gives a history of airline travel within the past 24 h. His parents are present at the bedside and volunteer that the patient and his wife were involved in a motorcycle crash 3 months ago in whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…In these patients, computed tomography (CT) shows a fresh hematoma within the CSDH, and the fresh hematoma has both a higher and of relatively more uniform density in comparison to the surrounding CSDH. This condition is termed acute-on-chronic SDH, a type of SDH with unique characteristics 31 33) . Patients with acute-on-chronic SDH have more hemostatic complications and more unfavorable outcomes.…”
Section: Symptoms Of Csdh In Elderly Patientsmentioning
confidence: 99%
“…In these patients, computed tomography (CT) shows a fresh hematoma within the CSDH, and the fresh hematoma has both a higher and of relatively more uniform density in comparison to the surrounding CSDH. This condition is termed acute-on-chronic SDH, a type of SDH with unique characteristics 31 33) . Patients with acute-on-chronic SDH have more hemostatic complications and more unfavorable outcomes.…”
Section: Symptoms Of Csdh In Elderly Patientsmentioning
confidence: 99%
“…Chronic haematomas are a mixture of liquefied blood and a semisolid clot pooling between the dura mater and the arachnoid mater [ 1 , 3 ]. Although the pathophysiology of ACSDH is complex and incompletely understood, it appears that rotational forces accompanying movement of the skull exert tensile strain and rupture of bridging veins leading to acute haemorrhaging into the subdural space [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found 8% of chronic SDH were actually acute-on-chronic SDHs. There are a few cases designated as acute-on-chronic SDH in the literature 5,8,9,16) . Curiously, it is hard to find any comments on the acute-on-chronic SDH, even in clinical series 3,12) reporting more than a thousand cases of chronic SDH.…”
Section: Discussionmentioning
confidence: 99%